EFEKTIVITAS AROMATERAPI LAVENDER UNTUK MENGURANGI MUAL MUNTAH PADA IBU HAMIL TRIMESTER I - Winsari, Wiwin; Yolandia, Rita Ayu; Lisca, Shinta Mona (Journal of Midwifery Tiara Bunda, 2023)
Nausea and vomiting that occurs in pregnancy is caused by increased levels of estrogen and progesterone hormones produced by Human Chorionic Gonadotropine (HCG). Nausea and vomiting occur in 60-80% of primigravida and 40-60% of multi gravida. Nausea and vomiting generally occur during the first trimester of pregnancy. One of the non-pharmacological management of nausea and vomiting is by giving lavender aromatherapy. The purpose of this study was to determine the effectiveness of lavender aromatherapy to reduce vomiting nausea in first trimester pregnant women. This study used a quasi-experimental method with a pre-test and post-test design with a control group. The sampling technique used was purposive sampling with a total sample of 34 pregnant women. The instrument used was a valid and reliable questionnaire. Data analysis using univariate and bivariate paired T test with SPSS version 23. Bivariate results obtained that lavender aromatherapy is effective in reducing nausea and vomiting in first trimester pregnant women at PMB Reni Apriyanti (p=0.00). Lavender aromatherapy is effectively used to reduce nausea and vomiting in pregnant women because it can stimulate sensory and receptors so that it can affect the work of the brain and nervous system then provide a sense of calm and comfort so as to provide relaxation and reduce nausea in pregnant women